The diversity of viral community in Sogatella furcifera revealed by meta-transcriptomics - Wang, Jihan; Zhu, Yu; Li, Dongyuan; Zheng, Xinyue; Chai, Chunlian; Zhang, Jie; Wu, Jianguo; Hu, Qun; Zhao, Shanshan (Frontiers in Microbiology, 2025)
IntroductionMetagenomic analyses has significantly advanced our understanding of viral evolution and their functions within organismal biology. In particular, exploring the virome of agricultural pests like the white-backed planthopper (WBPH) is essential for understanding their role as potential virus vectors and developing effective pest management strategies.MethodsTo explore viral diversity, we collected white-backed planthoppers (WBPHs) from nine sites spanning four Chinese provinces (Liaoning, Fujian, Guangxi, and Yunnan) and performed metagenomic sequencing.ResultsOur analysis identified 11 novel viruses belonging to 7 viral families, encompassing positive-sense single-stranded RNA (+ssRNA), negative-sense single-stranded RNA (-ssRNA), and double-stranded RNA (dsRNA) viruses. Remarkably, eight of the southern Chinese sites, excluding one in Liaoning province, contained a previously undiscovered Sobelivirales virus. Using rapid-amplification of cDNA ends (RACE), we determined the complete genome sequence of this novel Sobelivirales virus. Subsequent analyses of its encoded proteins, potential structural domains, and phylogenetic relationships suggested that it may belong to a new genus within the Sobelivirales. Small RNA sequencing confirmed viral replication in WBPH by revealing that virus-derived small interfering RNAs (vsiRNAs) were primarily 21 and 22 nucleotides long.DiscussionOur results have important implications for understanding virus carriage in WBPHs, evaluating their role as virus vectors, and informing the development of improved pest management strategies. Furthermore, this study highlights the power of metagenomics in uncovering novel viruses and expanding our knowledge of viral diversity.